Análise estrutural de complexos derivados de telúrio - Santos, Sailer Santos dos (2011)
This work describes the synthesis and structural analysis of different kinds of tellurium based compounds, depicting the preparation of zwitterions, coordination polymers and also heteronuclear complexes, using 4-ditellurobispyridine (4) and N , N , N , N -tetraethyl-N,N -pyridine-2,6-dicarbonyl-bis(thiourea) (12) as starting materials. These ligands are able to form complexes with tellurium allowing the simultaneous coordination of transition metals, producing novel compounds. The materials were characterized by single crystal X-ray diffraction, vibrational spectroscopy and 1H and 125Te nuclear magnetic resonance (when applicable). The methodology using the ligand 12 provided the preparation of three different classes of compounds: complexes with inorganic tellurium, complexes with organic derivatives of tellurium and tellurium based complexes with transition metals. The later ones are the most interesting owing the selectivity of the ligand, that coordinates to tellurium just with the softer site (sulfur atom), leaving the other donor atoms free to coordinate to another metallic center.